KECERDASAN PROFETIK BERBASIS DOA PARA NABI DALAM AL-QUR’AN - Abdul Aziem (LP2M Universitas PTIQ Jakarta, 2020)
The conclusion of this article is that the prophetic intelligence based on the prayers of the prophets in the Koran is a holistic-integrality intelligence that collects spiritual, emotional, intellectual, adversity, physical and naturalistic intelligences. Indicators of prophetic intelligence based on the prayers of the prophets include: 1) Self renewal through repentance; 2) The habit of praying for oneself, family and society; 3) Be grateful; 4) Affection; 5) Tawakal; 6) Choosing comrades in arms; 7) Printing a quality generation; 8) Love the motherland; 9) Develop scientific insights; 10) Skills to solve problems; 11) Communication skills; 12) Be patient; 13) Think positively; 14) Establishing prayers; 15) Performing Hajj; 16) Prospering the mosque; 17) Produce useful works; 18) Therapy with water; and 19) Herbal therapy. The method used in this research is qualitative method. This method is used to produce descriptive data, where the results are presented in a qualitative form. The method of interpretation used in this research is descriptive-thematic (mawdhūʻī).